Study of Student’s Perception in Learning Vocabularies Through Budi Harjo’s Challenge at Tik Tok - Arina, Sania (Discovery, 2024)
In the word of learning innovation is intended here to be anything fresh and qualitative improvement, of course there is something that differs from what existed before and is intentionally made to develop in the attempt to achieve learning objectives. In the meantime, what is implied by the term "new" in that case is linked to something that the receiver of the invention has not learned or applied. This study explores students’ perception in learning vocabularies through a challenge in a Tik tok platform. By doin this reasearch, the writer intends to find out 1) student’s perception in learning vocabularies through @budy harjo’s challenge at tik tok by learning through #duet in Tik Tok and 2) know the process of learning vocabularies @budy harjo’s challenge at Tik Tok through student’s perception. In this study, the researcher focuses on fifteen students whom join the @Budiharjo’s challenge for learning vocabularies at Tik Tok, the observer confined as an e-learning platform by using #duet and #learning vocabularies at Tik Tok. The observer adresses one main aspect; these are the implementation of speaking through #duet at Tik Tok as e-learning platform implemented in English learning based on four stages.